Ibrahim (Lelaki yang dilantik Tuhan sebagai Bapak Agama) rindu Allah / Wiwid Prasetyo ; editor Akhmad Muhaimin Azzet. - WIWID PRASETYO; Akhmad Muhaimin Azzet (Diva Press, 2011)
435 hlm. ; 20 cm [3 eks.]